PO215 Outcomes of neurology admissions to critical care. (1st December 2017) - Akbarian-Tefaghi, Ladan; Jenkins, Thomas; Davidson, Andrew
Abstract : Aims: To assess neurological admissions to the critical care unit in our centre according to published prioritisation criteria and evaluate predictors of outcome. Methods: We reviewed 39 patient records between November 2012-April 2015, and ranked from 1 to 4 according to prioritisation criteria. We evaluated predictors of outcome, including length of stay, using regression modelling. Results: 18 females and 21 males were assessed with a mean age of 41 years (range 23–83). Twelve patients had strokes, 6 status epilepticus, 16 neuromuscular disorders, 1 post-arrest hypoxia-ischaemia, 3 metabolic problems and 1 meningitis. Six patients had serious co-morbidities. Mean time from ward to critical care was 5 days (range 0–39), time on critical care was 10 days (0–45), and time from critical care to home 23 days (2–84). Sixty-six percent received non-invasive ventilation, 51% intubation and ventilation, 27% tracheostomy and 8% inotropes. 23 patients were classed priority 1, 9 priority 2 and 7 priority 3. Seventy-four percent survived to discharge to the ward and of these 93% went home. Of survivors, 62% had a Rankin score 1–2. All the priority 3 patients died. There was no association between length of stay and outcome. Conclusions: Neurological patients in critical care generally have good outcomes, even with prolonged stays. Meeting priority 3 criteria was associated with poor prognosis.